Removal of Iron and Manganese from Palm Oil Mill Effluent (POME) using Activated Clinoptilolite Zeolite. Issue 1 (May 2021) - Aziz, R A; Li, C K; Salleh, M N; Saleh, M
Abstract: The adsorption capacity of activated clinoptilolite zeolite for the removal of heavy metal ions; iron Fe(III) and manganese Mn(II) from palm oil mill effluent (POME) was investigated in this batch sorption study. The physicochemical properties of both raw clinoptilolite zeolite and POME effluent were first characterized before the modification of the zeolite is made, chemically and physically. The raw filtered POME has an initial pH of 4.56 which was acidic, whereas the natural zeolite has a slightly alkaline pH at 7.52. The effects of pH (5, 7 and 9), sorbent dosage (15, 20 and 25 g in 125 ml of effluent), contact time (15, 30, 45, 60, 120, 150, 180 and 200 minutes) and agitation speed (120, 150, 180 and 200 rpm) on the sorption of heavy metal ions were evaluated. The concentration of heavy metals was analyzed using AAS. The concentration of heavy metal ions for each parameter has decreased significantly after batch study. The adsorption of heavy metal ions increased with the increasing of pH and adsorbent dosages. Optimum percentage of metal removal and the amount of metal ions adsorbed by the zeolite were determined at 85% of Fe(III) and almost 92% of Mn(II) in the experiments.